Effects of high loading dose of clopidogrel in ST elevated myocardial infarction treated with fibrinolytic agent - Solmaz, Hatice; Akbulut, Mehmet; Korkmaz, Hasan; Yavuzkir, Mustafa F.; Kaya, Oguz K.; Kurtoglu, Ertugrul; Uysal, Ayhan (My University, 2013)
Purpose: The purpose of the present study was to evaluate the effects of different loading doses of clopidogrel on ST segment resolution on ECG, changes in cardiac enzyme levels and serum levels of high-sensitivity C-reactive protein (Hs-CRP) in patients with ST elevated myocardial infarction (STEMI) treated with fibrinolytic therapy. Methods: Patients admitted to our cardiology clinic with a diagnosis of STEMI and treated with fifibrinolytic therapy were included: Group 1 (n=58) received a 300 mg loading dose of clopidogrel, Group 2 (n=55) a 450 mg loading dose and Group 3 (n=59) a 600 mg loading dose. A 75 mg/d maintanence dose of clopidogrel was given in all groups. Results: All demographic characteristics and baseline laboratory parameters were statistically similar among three groups (p>0.05). When ST resolution periods were compared, most patients in Group 3 had ST resolution at 30 minutes; Group 2 at 60 minutes and Group 1 at 90 minutes (p<0.05). Peak levels of creatine kinase (CK) and CK-MB were as follows: Group 3, 8th hour, Group 1 and 2, 12th hour. Peak levels of those enzymes were significantly lower in Group 3 than in Group 1 and 2 (<0.05). Although basal hs-CRP levels of all groups were similar, the increase in hs-CRP levels at 48 hours was lower with higher clopidogrel loading doses (p<0.05). Conclusion: In this study comparing three different clopidogrel loading doses, the higher doses provided earlier ECG resolution, earlier and lower peak CK and CK-MB levels and lower levels of hs-CRP. © 2013 CIM.
Keywords: Aged; C-Reactive Protein; Drug Administration Schedule; Electrocardiography; Female; Fibrinolytic Agents; Humans; Male; Middle Aged; Myocardial Infarction; Ticlopidine; C reactive protein; clopidogrel; drug derivative; fibrinolytic agent; ticlopidine; aged; article; drug administration; electrocardiography; female; heart infarction; human; male; metabolism; middle aged